The Relationship between Nutritional Status, Age of Menarche, and Physical Activity with Polymenorrhea in Female Students of Kader Bangsa University, Palembang in 2024 - Dea Novaliani; Fika Minata Wathan; Erma Puspita Sari; Minarti Minarti (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Polymenorrhea is a menstrual cycle disorder â‰¤ 21 days that often occurs in adolescents, this problem can arise due to poor nutritional status, early age of menarche and heavy physical activity. The purpose of this study was to determine the relationship between nutritional status, age of menarche, and physical activity with polymenorrhea in female students of Universitas Kader Bangsa Palembang in 2024. Quantitative research method with cross-sectional research design. The sampling technique used Accidental Sampling. The population in this study were all female students of Universitas Kader Bangsa who came on June 4-5, 2024 and the sample used was 54 respondents. The data source came from primary data. Data analysis used univariate and bivariate. The results of this study showed that of the 54 respondents who filled out the questionnaire, as many as (22,2%) experienced abnormal nutritional status, (3,7%) early menarche, and (18,5%) heavy physical activity. As many as (20,4%) experienced polymenorrhea and (79,6%) did not experience polymenorrhea. The conclusion of this study is that there is a relationship between nutritional status and physical activity with polymenorrhea and there is no relationship between age of menarche and polymenorrhea in female students of Universitas Kader Bangsa Palembang in 2024.